Sustainable TVET Teacher Education Program Instrument: Instrument Validation - Hamdan, Nor Hidayah; Yunos, Jailani Md; Sern, Lai Chee; Ibrahim, Badaruddin (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to construct-validate an instrument of sustainable TVET Teacher Education program. The sustainable domains and elements measured were derived from previous study of instrument development. Fifty questionnaires were distributed to TVET-TE lecturers from Institute of Technical Teacher Training, which lasted for a week and 31 questionnaires had returned within the timeframe. The Rasch Measurement Model through Winstep version 3.69.1.11 was used for analysis to get the construct validation. There were three parameters referred to namely reliability and separation index item-person; statistical fit; and standardised residual correlation for item dependent. This parameter were used to measure the item fit and redundancy. The Cronbach’s alpha of the instrument was highly reliable at 0.99 make it highly reliable to be used. All items indicate a positive value for item polarity. The analysis indicates 24 items can be dropped from the instrument for being misfit, and nine pairs of items has been identified to be redundant. Overall, 24 items were drop and five items were kept with revision, making the final instrument consisted of 93 items in total. In conclusion, the instrument is valid an applicable for the real study. It is in a hope that this study can contribute towards the development and improvement on the sustainability of TVET Teacher Education program.